2006
DOI: 10.1158/1078-0432.ccr-05-1574
|View full text |Cite
|
Sign up to set email alerts
|

Mannan-MUC1–Pulsed Dendritic Cell Immunotherapy: A Phase I Trial in Patients with Adenocarcinoma

Abstract: Purpose: Tumor antigen-loaded dendritic cells show promise for cancer immunotherapy.This phase I study evaluated immunization with autologous dendritic cells pulsed with mannan-MUC1 fusion protein (MFP) to treat patients with advanced malignancy. Experimental Design: Eligible patients had adenocarcinoma expressing MUC1, were of performance status 0 to 1, with no autoimmune disease. Patients underwent leukapheresis to generate dendritic cells by culture ex vivo with granulocyte macrophage colony-stimulating fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
82
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(84 citation statements)
references
References 36 publications
1
82
1
Order By: Relevance
“…All kinds of modified DC approaches have been investigated to be applied in antitumor responses. It has been shown that protein-loaded DCs contain viral antigens and have antigen presentation capability that makes them become a potentially attractive vector for trigger T-cell antitumor responses (9)(10)(11)(12)40). However, there is no report about immunotherapy with specific CTL in NPC patients induced by DCs loaded with LMP2A protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All kinds of modified DC approaches have been investigated to be applied in antitumor responses. It has been shown that protein-loaded DCs contain viral antigens and have antigen presentation capability that makes them become a potentially attractive vector for trigger T-cell antitumor responses (9)(10)(11)(12)40). However, there is no report about immunotherapy with specific CTL in NPC patients induced by DCs loaded with LMP2A protein.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that DCs modification such as protein load can be successfully applied in tumor immunotherapy. DCs loaded with protein can promote cellular immunity both in experimental animal models and humans (8)(9)(10)(11). Optimal antigen loading strategies provide epitopes presented by both MHC class I and class II leading to a diverse immune response in which many clones of cytotoxic T cells (CTLs) and CD4 + T cells are involved (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of MUC1-targeted therapies in lung, prostate and ovarian malignancies (Loveland et al, 2006;North et al, 2006) show therapeutic promise. As the majority of epithelioid mesotheliomas demonstrate strong MUC1/epithelial membrane antigen (EMA) positivity by immunohistochemistry (Ordonez, 2003) similar anti-MUC1 therapeutic strategies may have potential in mesothelioma.…”
mentioning
confidence: 99%
“…Dendritic cell vaccines have been widely studied and are currently being applied for treatment of cancers. [21][22][23][24][25][26] Most investigations have focused on the major ability of DC based vaccines to stimulate CD8C T cells. 51,52 However, there is evidence as well that DC based vaccines can stimulate antigen specific B cells with the concomitant release of antibody.…”
Section: Discussionmentioning
confidence: 99%
“…20 Antigen-sensitized DCs have been evaluated as potential vaccines for cancer treatment. [21][22][23][24][25][26] Other clinical trials have also been performed to evaluate their potential utility against other disorders such as infectious diseases. 27,28 In fact, in animal studies, DCs sensitized with mutant Ab peptides were used to vaccinate different mouse models of AD, without eliciting a generalized inflammatory response.…”
Section: Introductionmentioning
confidence: 99%